Economic evaluation of atezolizumab in combination with bevacizumab and chemotherapy for metastatic, persistent, or recurrent cervical cancer in China: A cost-effectiveness analysis - Shuo Yang; Yibing Hou; Xiaohui Wang; Shuo Kang; Zhenhua Pan (PLoS ONE, 2026)
Background From China’s healthcare perspective, this analysis compared the cost-effectiveness of Atezolizumab in combination with Bevacizumab and chemotherapy for Metastatic, Persistent, or Recurrent Cervical Cancer. Methods A Markov model was developed to track patients’ transitions over 3-week cycles and evaluate the health and economic outcomes over a 10-year horizon for the two competing treatments. The survival data were gathered from the BEATcc trial, and cost and utility values were obtained from the published studies. Total costs, life-years, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratio (ICER) were the model outcomes. Sensitivity analyzes were performed to examine the robustness of the model results. Results In the base case, atezolizumab plus bevacizumab and chemotherapy yielded a marginal cost of $233,602.51 and an additional 0.54 QALYs, resulting in an ICER of $432,597.24 per additional QALY gained, which exceeded the willingness-to-pay (WTP) threshold of $36,859 in China. Sensitivity analyzes confirmed the robustness of the model outcomes. Conclusions Atezolizumab plus bevacizumab and chemotherapy was not a cost-effective treatment for patients with metastatic, persistent, or recurrent cervical cancer compared with bevacizumab plus chemotherapy from the perspective of the Chinese health-care system.